A new insight into CFTR allele frequency in Brazil through next generation sequencing. Issue 10 (3rd August 2017) - Nunes, Luisa M.; Ribeiro, Roberto; Niewiadonski, Vivian D.T.; Sabino, Ester; Yamamoto, Guilherme L.; Bertola, Débora R.; Gaburo, Nelson; da Silva Filho, Luiz Vicente R.F.
Abstract: Background: As of 2013, fewer than 20% of patients in the Brazilian CF Registry had two CFTR mutations identified. The aim of this study was to sequence the coding region of the CFTR in Brazilian CF patients and determine the frequency of mutations in this cohort. Methods: Patients with CF and those with suspected atypical CF or CFTR‐related disorders were invited to enroll. Total DNA was extracted from blood samples, quantified, and purified. Library preparation was performed using Ion Xpress™ Plus gDNA and Amplicon Library preparation kits (Life Technologies), as well as sequencing using the Ion Torrent platform (Life Technologies). Results: A total of 141 patients were enrolled, and 45 mutations were identified. Among 126 CF patients, we identified mutations in 97.2% of alleles. The three most common mutations were F508del, G542X, and 3120 + 1G‐>A. Five novel pathogenic mutations were also identified. Conclusions: Next generation sequencing (NGS) allowed the identification of mutations in most CF alleles and confirmed allelic heterogeneity in our population.